Emotional behavior and stress - qohrunnada widodo, Aulia ainus safina (Maliki Interdisciplinary Journal, 2025)
Stress and emotional behavior are two interrelated aspects in human psychological dynamics. When individuals face external pressures or internal demands, both the body and mind respond with various emotional reactions such as anxiety, anger, fear, and panic. These reactions are closely related to the fight or flight mechanism, which is regulated by the sympathetic nervous system and the limbic structures of the brain, particularly the amygdala and hypothalamus. This paper aims to analyze the relationship between emotions and stress, their causes and symptoms, and how the body responds to stressful conditions. Through theoretical review and literature analysis, it was found that stress can be adaptive or destructive depending on how individuals manage it. Proper stress management through self-awareness, emotional regulation, and social support can help individuals maintain psychological balance and improve their overall quality of life.